Cancer occurrence in Turner syndrome and the effect of sex hormone substitution therapy. Issue 1 (January 2021) - Viuff, Mette Hansen; Stochholm, Kirstine; Lin, Angela; Berglund, Agnethe; Juul, Svend; Gravholt, Claus Højbjerg
Abstract : Objective: Although the overall risk of cancer is not increased in Turner syndrome, the pattern of cancer occurrence differs from the general population. We aim to describe the cancer morbidity pattern in Turner syndrome and evaluate the effect of long-term hormone replacement therapy (HRT). Design: Nationwide epidemiological study. Methods: 1156 females with Turner syndrome diagnosed during 1960–2014, were linked with data from the Danish National Patient Registry. Statistics Denmark randomly identified 115 578 female controls. Stratified Cox regression was used to analyze cancer morbidity, mortality and effect of HRT. Results: Overall risk of cancer was not elevated (hazard ratio 1.04 (95% CI: 0.80–1.36)). The risk of skin cancer and benign skin neoplasms was two-fold increased, while the risk of breast cancer was decreased (hazard ratio 0.4 (0.2–0.9)). Turner syndrome (45, X) had a two- to five-fold increased risk of benign CNS tumors, colon and rectal cancers, benign skin neoplasms and skin cancer. Turner syndrome women with a 45, X/46, XX karyotype had an increased risk of tongue cancer. HRT had no impact on the risk of any cancer investigated in this study. Conclusions: The lack of one X chromosome might play a role in skin neoplasms, CNS tumors, colon and rectal cancers. The risk of breast cancer is lower than in the general population. Long-term HRT during the premenopausal age range seems not to exert a cancerous effect in Turner syndrome. Increased vigilance concerning specific types of cancer in Tuner syndrome harboring a 45, X karyotype is needed.